Are physical factors associated with poor prognosis following a whiplash trauma?: a protocol for a systematic review and data synthesis. Issue 11 (19th November 2019) - Alalawi, Ahmed; Gallina, Alessio; Sterling, Michele; Falla, Deborah
Abstract : Introduction: Mitigating the transition from acute to chronic whiplash-associated disorders (WAD) is fundamental, and this could be achieved through early identification of individuals at risk. Several physical factors such as angular velocity, smoothness of neck movement and coactivation of neck flexors and extensors, have been observed in patients with WAD, but their predictive ability after a whiplash injury have not been considered in previous reviews. Therefore, the aim of the current protocol is to outline the protocol for a systematic review that synthesises the current evidence of which physical factors can predict ongoing pain and disability following a whiplash trauma. Methods and analysis: Two independent reviewers will search for studies in several electronic databases including MEDLINE, Embase, CINAHL, PsycINFO, Scopus and Web of Science as well as grey literature. Observational cohort studies will be considered if they involve participants with acute WAD followed for at least 3 months post-injury. Studies will be required to assess the prognostic ability of one or more physical factors that directly involve a body function and/or structure and can be measured objectively. Further, patient-reported outcomes of physical function will be considered. The primary outcome for this review is Neck Disability Index, while all other validated measures will be considered as secondary outcomes. Risk of bias across individual studies will be assessed using the Quality In Prognostic Studies tool along with the Grades of Recommendation, Assessment, Development and Evaluation method to assess the quality of evidence. A meta-analysis will be conducted depending on homogeneity and the number of available studies. If appropriate, data will be pooled and presented as odds ratios, otherwise, a qualitative synthesis will be conducted. Ethics and dissemination: Ethical approval is not required for this systematic review. The result from this review will be published in peer-reviewed journals. PROSPERO registration number: CRD42019122559